Loss of LLGL1 Expression Correlates with Diffuse Gastric Cancer and Distant Peritoneal Metastases - Alexander Desuki; Frank Staib; Ines Gockel; Markus Moehler; Hauke Lang; Stefan Biesterfeld; Annett Maderer; Peter R. Galle; Martin R. Berger; Carl C. Schimanski (Canadian Journal of Gastroenterology and Hepatology)
Background. Loss of LLGL1 has been associated with loss of cellular adhesion and dissemination of cells from colorectal cancer and malignant melanoma. Regulation and relevance of LLGL1 were analyzed in gastric cancer patients with lymphatic and distant dissemination. Furthermore, LLGL1 expression was analyzed in relation to the cellular adhesion protein E-cadherin. Methods. LLGL1 and E-cadherin transcription levels were evaluated in 56 gastric cancer patients and five gastric cancer cell lines. IHC staining for LLGL1 was performed on 39 gastric cancer specimens. LLGL1 was stably transfected into LLGL1 negative gastric cancer cell line SNU16 (del(17) (p11.2)) for functional in vitro assays and a xenograft bioassay. Results. Gastric cancer specimens and cell lines displayed LLGL1 and E-cadherin expression levels with variable intensity. In gastric mucosa, LLGL1 exhibited weak cytoplasmic and strong cortical staining. Loss of LLGL1 expression occurred in 65% of gastric cancers and significantly correlated with loss of E-cadherin expression (P=0.00009). Loss of LLGL1 expression was associated with the diffuse type of gastric cancer (P=0.029) with peritoneal carcinomatosis (M1; P=0.006) and with female gender (P=0.017). Stable reexpression of LLGL1 in SNU16 cells significantly increased both plastic surface adhesion and extracellular matrix proteins laminin and fibronectin, but had no impact on in vitro proliferation, apoptosis, or invasion or on in vivo proliferation or differentiation in our xenograft bioassay. Conclusion. LLGL1 is coexpressed with E-cadherin. Loss of expression of either protein is associated with diffuse gastric cancer and peritoneal metastases. LLGL1 does not impact on proliferation or epithelial-mesenchymal transition (EMT) rather increasing cellular adhesion.